Application of artificial neural network (ANN) for reactive power dispatch / Siti Rokiah Ramli - Ramli, Siti Rokiah (2003)
Recently research has shown that ANN is promising solution to many applications especially for non-linear problem in power system, which is difficult for conventional technique. The potential of application of ANN as an alternative approach for solving certain difficult power system problem where conventional methods have not achieved desired speed couldn't be understated. This report presents the study of reactive power dispatch problem, for the power system to operate in a reliable and economic way. In this study, artificial neural network (ANN) with multilayer feed forward and error back propagation is used. The feed forward network programmed was developed using the MATLAB version 6.1. The proposed technique is tested on IEEE 14 bus system. The result shows that the proposed ANN technique is highly accurate and capable to predict at faster rate.